Hungary : Long-term Poverty, Social Protection, and the Labor Market, Volume 2. Technical Papers - World Bank (Washington, DC, 2013)
This report documents the emergence of a group of long-term poor in Hungary. While growth will continue to be necessary to create well-paying jobs that would enable people to escape poverty, the long term poor are not likely to benefit from growth since they are detached from the labor market, socially excluded, and in many cases, facing discrimination which keeps them from reintegrating into the labor market. The long-term poor in Hungary are comprised of several distinct social groups: the homeless, rural population particularly those living in micro-communities, unemployed or withdrawn from the labor market, households with more than three children, single parent families, single elderly females, and the Roma. A third of the long-term poor are of Roma ethnicity, even though this group is only approximately 5 percent of the Hungarian population. The analysis of the labor market confirms the connection between long-term unemployment and long-term poverty. One of the messages of this report is that the Roma need good-paying jobs first and foremost. Many Roma villages are characterized by a cycle of dependency on state transfers. Reinsertion programs are needed to break this cycle. In the medium term, emphasis on providing high-quality general education to the Roma is needed. These challenges for Hungary are complicated by decentralization, which may lead to unequal treatment of the poor, with less financing available where social programs are most needed.